2004
DOI: 10.1111/j.1095-8339.2004.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Karyological studies in Tripleurospermum (Asteraceae, Anthemideae) from north-east Anatolia

Abstract: Chromosome number and morphology in 14 taxa belonging to 19 populations of Tripleurospermum Sch. Bip. were studied using karyological and numerical taxonomical techniques. Data on chromosome measurements were analysed using cluster analysis. Chromosome numbers of these taxa are 2 n = 2 x = 18, 4 x = 36 and 5 x = 42-48. Seven records are new, two are not consistent with previous counts, and the remainder confirm the very limited previous data (one to three records). A new ploidy level (pentaploidy) is reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 10 publications
(13 reference statements)
7
26
0
Order By: Relevance
“…However, further investigations are needed to determine the nature of polyploidy in the taxon. Polyploidy is regarded by many authors as an important evolutionary mechanism in plants (Bretagnolle et al 1998;Soltis et al 2004) and in some groups of the Anthemideae in particular (Solbrig 1977;Vallès et al 2001Vallès et al , 2005Inceer and Beyazoglu 2004;Guo et al 2005;Inceer and Hayirlioglu-Ayaz 2007). This statement does not reflect what happens in the genus.…”
Section: Systematic Implicationsmentioning
confidence: 76%
“…However, further investigations are needed to determine the nature of polyploidy in the taxon. Polyploidy is regarded by many authors as an important evolutionary mechanism in plants (Bretagnolle et al 1998;Soltis et al 2004) and in some groups of the Anthemideae in particular (Solbrig 1977;Vallès et al 2001Vallès et al , 2005Inceer and Beyazoglu 2004;Guo et al 2005;Inceer and Hayirlioglu-Ayaz 2007). This statement does not reflect what happens in the genus.…”
Section: Systematic Implicationsmentioning
confidence: 76%
“…All the studied taxa had the basic chromosome number of x = 9 (Table 1), predominant in tribe Anthemideae and the family Asteraceae (Inceer and Beyazoglu 2004 and references cited therein; Valles et al 2005;Inceer et al 2012). Seven taxa were diploid with 2n = 18, and two taxa were tetraploid with 2n = 4x = 36.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome counts in many members of Anthemideae have already been reported (e.g. Torrell et al 2001;Inceer and Beyazoglu 2004;Vallès et al 2005;Garcia et al 2006;Inceer et al 2007Inceer et al , 2012Li et al 2008;Chehregani and Mehanfar 2008;Chehregani and Hajisadeghian 2009;Chehregani et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Ozcan et al (2011) the diverging karyological results may arise from intraspecific karyological differentiation. Hayırlıoglu-Ayaz and Beyazoglu (2000) and Inceer and Beyazoglu (2004) reported that specimens collected from various geographical regions have different chromosome numbers.…”
Section: Discussionmentioning
confidence: 99%